Successful Surgical Separation of Craniopagus Twins - A Monumental Achievement in the History of Bangladesh - Salek, Md Al Amin; Hasan, Masroor; Ahmed, Masud; Beauty, Anjuman Ara; Islam, Md Shafiqul; Kalam, Md Abul (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Craniopagus is a condition of conjoined twins that are fused at the cranium. After birth, 25% of craniopagus twins survive and can be considered for surgical separation. It is a complex multistage, multidisciplinary team involvement exercise needing detailed evaluation, planning and preparation beforehand. A harmonious collaboration from the clinical, administrative as well as logistic point of view is mandatory for successful management of such complex condition. The honorable prime minister of Bangladesh picked up “Rabeya and Rukaiya”, a craniopagus twins, the first ever case in the history of Bangladesh and handed them over to an expert team from Hungary and Bangladesh for successful management. The noble joint exercise known as “Operation Freedom” took place in home and abroad through multiple procedures/interventions in different institutions by a group of experienced panels of medical and non-medical professionals. In this article we will highlight the events of this monumental achievement. J Bangladesh Coll Phys Surg 2022; 40: 121-125